Different domains of physical activity: The role of leisure, housework/care work, and paid work in socioeconomic differences in reported physical activity. (April 2019) - Cusatis, Rachel; Garbarski, Dana
Abstract: Inequality in socioeconomic status (SES)—education, income, and occupation—may further exacerbate the health gap between the "haves" and "have nots" by shaping health behaviors such as physical activity. For example, those in higher socioeconomic positions are consistently found to engage in more physical activity according to public health reports that focus on leisure activity. However, previous research investigating the role of SES in shaping engagement in housework, childcare, and paid work suggests different opportunities for physical activity. This discrepancy in how researchers ask questions about physical activity and the pathways people take to healthy activity raises the question: Do socioeconomic differences in physical activity look different when we look at other domains of physical activity beyond leisure? And, does how we measure SES matter? We draw on data from the American Time Use Survey (ATUS) to assess the roles of education, income, and occupation in the amount of time individuals spend in different types of physical activity. Results demonstrate that socioeconomic differences in physical activity change depending on the activity domain and, therefore, when all domains of physical activity are accounted for compared to leisure-only. Further, the measurement of SES matters: key indicators of SES (education, income, and occupation) have varying associations with levels and types of physical activity. Findings from this research have important implications for the assessment of physical activity across SES, ultimately impacting survey research and public health. Highlights: Leisure questions of physical activity may not capture socioeconomic impacts on access and opportunity for activity. Less educated report more time in house/care and paid work compared to more educated. Higher income is associated with more reported leisure and less house/care work. Different occupations report significantly different amounts of activity at paid work. Socioeconomic differences in activity are contingent on domain of activity and SES indicator.